An evaluation of effect of hydroxyurea on frequency of blood transfusion, vaso-occlusive crisis and hospitalisation in children of sickle cell anemia - Gupta, Shikha; Choudhary, Prachi; Singh, Devraj; Malpani, Preeti (International Journal of Contemporary Pediatrics, 2022)
Background: Hydroxyurea therapy is a known effective and safe therapy for the treatment of sickle cell anemia (SCA). Although it is used worldwide in our Indian based setup, it is underutilized not only due to economic reasons but also due to unaware practitioners about its use. Methods: An ambispective observational study was performed at our tertiary care center over a period of 1 year 8 months. One hundred and ninety patients were enrolled after taking a complete history, then started on Hydroxyurea and followed up every 2 months till 1 year. On follow-up, frequency of vaso-occlucive crisis, blood transfusion and hospitalization were noted along with routine investigations and for any side effects. Results: Of 190 total recruited patients, 84 were studied at the end because of loss to follow-up due to various reasons. Significant decrease in the frequency of vaso-occlusive crisis (VOC), blood transfusion and hospitalisation were observed within 1 year of starting hydroxyurea (p<0.05). Conclusions: The use of hydroxyurea in our native population at our setup can decrease the frequency of vasooccluisve crisis, blood transfusion and hospitalisation in sickle cell patients.